2015
DOI: 10.1002/jhet.2578
|View full text |Cite
|
Sign up to set email alerts
|

3‐(3,5‐Dimethyl‐1H‐Pyrazol‐1‐yl)‐3‐Oxopropanenitrile as Precursor for Some New Mono‐Heterocyclic and Bis‐Heterocyclic Compounds

Abstract: 3‐(3,5‐Dimethyl‐1 H ‐pyrazol‐1‐yl)‐3‐oxopropanenitrile 1 was used as a cyanoacetylating agent for synthesis of the acetanilide derivative 3. Compound 3 was utilized as a key intermediate for the synthesis of some new mono‐chromene and di‐chromene derivatives 9 and 13, the dihydrazo derivatives 15, and the dithiazole derivatives 18 via the condensation with o‐hydroxybenzaldehyde derivatives, the coupling with aryl diazonium salts, or the reaction with phenyl isothiocyanate in presence of KOH followed by phenacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The ultrasonic method afforded the products in less reaction time with high yields and purities, as shown in Table . The spectral data of the products (Figures S2–S4, Supporting information) agreed with the reported data [ref for compound 6 : mp 225 °C, yield 91%; ref for compound 9 : 267–269 °C, yield 90%].…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The ultrasonic method afforded the products in less reaction time with high yields and purities, as shown in Table . The spectral data of the products (Figures S2–S4, Supporting information) agreed with the reported data [ref for compound 6 : mp 225 °C, yield 91%; ref for compound 9 : 267–269 °C, yield 90%].…”
Section: Resultssupporting
confidence: 87%
“…White solid in yields 88% (conventional heating, 4 h) and 95% (US, 20 min), mp 226–227 °C [ref : 225 °C, yield 91%]. 1 H NMR (400 MHz, DMSO- d 6 ) δ: 2.49 (s, 3H, CH 3 ), 3.92 (s, 2H, CH 2 ), 7.64 (d, 2H, J = 8.8 Hz, Ar), 7.42–7.91 (d, 2H, J = 8.8 Hz, Ar), 10.59 (s, 1H, NH) ppm; 13 C NMR (100 MHz, DMSO- d 6 ) δ: 26.5, 27.0, 115.6, 118.5, 129.7, 132.3, 142.6, 161.7, 197.6 ppm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account the aforementioned data and as an extension of our ongoing research work on the designing biologically active heterocyclic products that act as anticancer agents and others, [63–77] herein we adopted design and synthesis of new compounds containing thiazolidinone scaffold. Thiazolidinones 3 a , b were synthesized from the starting thiosemicarbazones 2 a , b , then 3 a , b undergoing Knövenagel condensation with different aryl and heteryl aldehydes by two‐steps or multicomponent route to afford three series of thiazolidinones 5 a – j , 7 a – h and 9 a – j bearing substitution at position‐5 as seen in Figure 3.…”
Section: Introductionmentioning
confidence: 99%
“…[60][61][62] On the other hand, Raslan et al [43] have reported synthesis of compounds containing benzoate moiety exhibiting better inhibition in HepG2 growth with IC 50 = 8.90 μM besides inhibiting EGFR protein kinase with IC 50 = 0.124 μM, in addition to a scientific article reported the synthesis of trimethoxy phenyl benzoate containing derivatives displaying anticancer activity and inhibitory activity against EGFR. [44] Taking into account the aforementioned data and as an extension of our ongoing research work on the designing biologically active heterocyclic products that act as anticancer agents and others, [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77] herein we adopted design and synthesis of new compounds containing thiazolidinone scaffold. Thiazolidinones 3 a, b were synthesized from the starting thiosemicarbazones 2 a, b, then 3 a, b undergoing Knövenagel condensation with different aryl and heteryl aldehydes by two-steps or multicomponent route to afford three series of thiazolidinones 5 a-j, 7 a-h and 9 a-j bearing substitution at position-5 as seen in Figure 3.…”
Section: Introductionmentioning
confidence: 99%